Inclusion Complexation of Lansoprazole with Cyclodextrin Derivatives by 1H NMR, UV Spectroscopy and Phase Solubility - Fang1, H.Y.; Jiang1, X.Y.; Zhou2, C.S.; Tang2, K.W.; Yang2, T.; Zhang2, P.L. (Asian Journal of Chemistry, 2014)
The inclusion complexes of cyclodextrin derivatives with lansoprazole (LPZ) in aqueous solution were investigated by proton nuclear magnetic resonance (1H NMR) spectroscopy, ultraviolet (UV) spectroscopy and phase solubility analysis. The main factors affecting the inclusion process, such as the structure and concentration of host molecule, temperature and pH, were discussed. A dependable determination of the complex stoichiometry was offered by the continuous variation technique. Thermodynamic parameters for inclusion process of lansoprazole and hydroxypropyl-b-cyclodextrin (HP-b-CD) were also investigated. The chemical shifts of protons of lansoprazole by 1H NMR showed that benzimidazole group was inserted into the cavity of cyclodextrin derivatives. The ultraviolet spectroscopy and phase solubility diagram results revealed that the formation of inclusion complexes with a stoichiometric ratio of 1:1.